TERMO CIRCUNSTANCIADO DE OCORRÊNCIA LAVRADO PELA POLÍCIA RODOVIÁRIA FEDERAL: UMA ANÁLISE LEGAL E CONSTITUCIONAL - SOUSA, JUCELIO URTIGA DE (2020)
Law 9.099/95 introduced into the Brazilian legal system a new regulation for less complex cases, creating the microsystem of Special Civil and Criminal Courts for processing and judging these cases within the states. In the criminal field, the antiderretimento law instituted the detailed term of occurrence (TCO) as a piece to record infractions of lesser offensive potential, with the “police authority” being responsible for their drawing up and forwarding them to the Judiciary. In view of the breadth of this expression, several states allow, through agreements and decrees, that their ostensive police carry out the procedure under the understanding that such piece is merely investigative, and is not the exclusive responsibility of the judicial police. However, this conduct is highly questioned, and there is a great deal of doctrinal and jurisprudence in the country regarding the competence to draw up this piece of information. In this perspective, there is a need for an analysis of the legality and constitutionality of the drawing up of TCOs by the agents of the ostensive police, notably the Federal Highway Police. For this, the deductive method is used as a method of approach, historical and interpretative methods as methods of procedure, and bibliographic and documentary research as a research technique, through which it was possible to construct the theoretical framework. The present study has as main objective to demonstrate the link between the real intention of the legislator, through the principles present in law 9.099 / 95 and the possibility of drawing up the TCO by the Federal Highway Police.